As correntes interacionistas e a sua repercussão nas teorias de Anthony Giddens e Bruno Latour - Karine Pereira Goss (Ciências Sociais Unisinos)
The article discusses three important qualitative currents critical of functionalism: social phenomenology, symbolic interactionism and ethnomethodology. Initially it introduces the main theories and authors that influence each one of those approaches. Then it describes the main theoretical and methodological assumptions of each one of them, their common aspects and most important representatives. Then it analyzes the role they ascribe to the actors cognition, as this is one of the basic principles that is common to the three of them. The article also tries to demonstrate how two contemporary sociologists Anthony Giddens and Bruno Latour who are heirs of different sociological traditions share some of the main precepts of those approaches. Finally, besides reflecting on the contributions that the three currents have given to social science, it stresses that one of the ways for sociology to recover a creative perspective is to retrieve the theoretical knowledge in conjunction with the empirical study developed by interactionist schools.